Teenage Motherhood and Long-run Outcomes in South Africa - Siv Gustafsson; Seble Worku (Tinbergen Institute, 2007)
Teenage motherhood is very high in South Africa. In 2001, 55 per thousand African South African women and 82 per thousand Coloured South African women were teenage mothers as compared to 8 among Indian South Africans and 3 among White South African women. In this paper we use the South African General Household Survey data of 2002 with complete retrospective fertility history to study teenage childbearing and a number of outcomes in 2002 such as completed high school and satisfaction with life. Our main findings are that teenage childbearing is negatively correlated with completing high school, but most other outcome measures do not show the negative effects from teenage motherhood as has been found in many previous US and UK studies. We estimate a bivariate probit model on the joint determination of the probability of teenage motherhood and completing high school, identifying by abortion rates and the numbers of doctors and nurses by region.
Keywords: D1; J1; 330; Teenage motherhood; high school completion; endogeneity; bivariate probit; South Africa; Mütter; Jugendliche; Lebenseinkommen; Probit-Modell; Südafrika